2011
DOI: 10.4103/0976-237x.83067
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between maternal periodontitis and preterm low birth weight: A case-control study

Abstract: Background:The relationship between periodontal diseases in pregnancy and children born prematurely or with low birth weight has been increasingly investigated, showing positive and negative results, respectively. Objective: To evaluate the association between Maternal Periodontitis and Preterm delivery or Low Birth Weight.Materials and Methods:In this case-control study, 104 pregnant women without systemic disease or other risk factors for preterm labor were chosen. The control group (n = 52) had term labor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
5
17
0
3
Order By: Relevance
“…The association demonstrated between maternal periodontal disease and LBW (Table ) corroborates some previous studies showing that maternal periodontal disease promotes adverse pregnancy outcomes, such as LBW and premature birth . Notwithstanding, other studies have failed to find effects of maternal periodontal disease on birth weights of offspring .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The association demonstrated between maternal periodontal disease and LBW (Table ) corroborates some previous studies showing that maternal periodontal disease promotes adverse pregnancy outcomes, such as LBW and premature birth . Notwithstanding, other studies have failed to find effects of maternal periodontal disease on birth weights of offspring .…”
Section: Discussionsupporting
confidence: 88%
“…The association demonstrated between maternal periodontal disease and LBW ( Table 2) corroborates some previous studies showing that maternal periodontal disease promotes adverse pregnancy outcomes, such as LBW and premature birth. 13,[30][31][32] Notwithstanding, other studies have failed to find effects of maternal periodontal disease on birth weights of offspring. 14,33 Ide and Papapanou 6 considered this association modest but significant, because in each study there is a high degree of variability in the evaluation of the populations as well as differences in the way the data are recorded and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Mannem and Chava concluded that both prior abortions and prior preterm labour were not significantly associated with the incidence of periodontitis. 8 In the present study, 15% and 38% of women in the case and control groups had previous term birth. Gandhimadhi in the case group and all patients in the control group had previous term birth.…”
Section: Discussionmentioning
confidence: 94%
“…Substantial evidence suggests a direct link between periodontal disease in pregnant women and adverse pregnancy outcomes (PITIPHAT et al, 2008;MICHALOWICZ et al, 2011;PISCOYA et al, 2012;KUNNEN et al, 2014). Periodontal disease affects more than 40% of pregnant women (LIEFF et al, 2004) and has been linked to adverse pregnancy outcomes, such as preterm delivery (OFFENBACHER et al, 1996;MANNEM;CHAVA, 2011;BOBETSIS et al, 2006;TUCKER, 2006), smaller fetuses (COLLINS et al, 1994;KOTHIWALE et al, 2014), pre-ecclampsia (PATTANASHETTI et al, 2013MISRATH BANU;RAMAMURTHY, 2014), fetal loss (XIAO et al, 2013), and late miscarriage (MOORE et al, 2005) in the parental generation. However, all of these reproductive impairments have only been studied in the parental generation and not in subsequent generations.…”
Section: Introductionmentioning
confidence: 99%